ADVANTAGES AND DISADVANTAGES OF LEARNING REPORT TEXT USING YOUTUBE VIDEOS IN PANDEMIC - Fairuz Jannah, Nud'ah (Wiralodra English Journal, 2021)
This study focuses on the advantages and disadvantages of learning report text using YouTube video in Covid-19 Pandemic. The purpose of this study was to find out the advantages and disadvantages of online learning using YouTube video media during the covid-19 pandemic through student opinions about learning taking place. This study uses a qualitative descriptive method, in which this study describes students' opinions through questionnaires and interviews that have been conducted by researchers. The participants of this study were 56 students who took part in the interview and 14 students who took part in the interview, all participants were taken from the twelfth class of hotel accommodation at SMK N 4 Yogyakarta. The results of this study indicate that in learning report text using YouTube media has advantages and disadvantages. The students give a positive response to the number of benefits that can be obtained during the learning process, even though the losses that can be obtained are also quite a lot.